1995
DOI: 10.1021/bi00001a037
|View full text |Cite
|
Sign up to set email alerts
|

Role of H1 in Chromatin Folding. A Thermodynamic Study of Chromatin Reconstitution by Differential Scanning Calorimetry

Abstract: In a series of related papers, we have recently presented the results of a thermodynamic approach to the conformational transitions of bulk chromatin induced in vitro by different structure-perturbing agents, such as the intercalating dye ethidium bromide or the ionic strength. In all these studies, we took advantage of the capability of differential scanning calorimetry to detect the changes in the melting behavior of the structural domains of chromatin (the linker and the core particle) associated with the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…Moreover, this configuration strongly favours a second compaction step, ensured by the attractive interactions between nucleosomes (or rather chromatosomes) that arise when the nuclesome faces are close enough. We in particular recover in this scheme the two-stage compaction of the 30-nm chromatin fiber observed experimentally [46] [47]. An insight on this interaction-induced compaction can be obtained by setting the effective parameters r nucl and H to 0, thus mimicking the enhanced influence of linker histone at high salt; in this case, P decreases to about 6 nm, indicating that nucleosomes actually stack very closely onto each other and lead to a superstable (and presumably rigid) fiber.…”
Section: B a Novel Chromatin Structurementioning
confidence: 62%
“…Moreover, this configuration strongly favours a second compaction step, ensured by the attractive interactions between nucleosomes (or rather chromatosomes) that arise when the nuclesome faces are close enough. We in particular recover in this scheme the two-stage compaction of the 30-nm chromatin fiber observed experimentally [46] [47]. An insight on this interaction-induced compaction can be obtained by setting the effective parameters r nucl and H to 0, thus mimicking the enhanced influence of linker histone at high salt; in this case, P decreases to about 6 nm, indicating that nucleosomes actually stack very closely onto each other and lead to a superstable (and presumably rigid) fiber.…”
Section: B a Novel Chromatin Structurementioning
confidence: 62%
“…Due to its sharp subdivision into two basic supramolecular domains (the linker and the core particle) the polynucleosomal chain lends itself to conformational studies by DSC. Therefore, this technique is a powerful tool for investigating the overall organization of chromatin in situ (10,12,13,(25)(26)(27). The thermal denaturation profile of interphase nuclei shows two major heat absorption peaks (labeled IV and V in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent paper, we have shown that the nucleosomes interact weakly in the 30-nm fiber. The experimental value of the interaction free energy is as low in magnitude as Ϫ5 kcal/ nucleosome mole (10), so that even limited biochemical modifications of the histone complement could result in a structural change. In this report we show that the basic conformational feature of chromatin in apoptosis is the tight face-to-face packaging of nucleosomes, which might be related to the increase in the amount of the unacetylated forms of histones H3 and H4 occurring in the course of condensation.…”
mentioning
confidence: 99%
“…After staining with Coomassie brilliant blue the amounts of histones were determined by scanning the gels as already reported [Cavazza et al, 1991;Russo et al, 1995]. The same procedure was used to evaluate the fraction of trypsinized histones.…”
Section: Electrophoretic Characterization Of the Dna Fragments And Ofmentioning
confidence: 99%
“…This correlation was established by exploiting the extraordinary capability of differential scanning calorimetry (DSC) to distinguish between the condensed and the unfolded state of the genome [Nicolini et al, 1983]. Using DSC, we and other groups were indeed able to characterize the thermodynamics of salt induces condensation [Cavazza et al, 1991;Labarbe et al, 1996], to elucidate the mechanism of binding of H1 to core chromatin [Russo et al, 1995], to describe the all-or-none structural transition which occurs inside the chromatin loop [Balbi et al, 1999] and to identify the role of histone acetylation [Gavazzo et al, 1997] and of the nuclear envelope [Spadiliero et al, 2002], respectively, in the modulation of chromatin higher order structure.…”
mentioning
confidence: 99%